Juvenile Dermatomyositis : A Case Report - Chowdhury, Pranab Kumar; Alam, Mansurul; Karim, Mohammed Rezaul; Das, Aparup Kanti; Mahmood, Nasiruddin; Ghosh, Sankar Kumar (Journal of Chittagong Medical College Teachers' Association, 2012)
Juvenile Dermatomyositis, most common pediatric inflammatory myopathies, distinguished by characteristic rash and proximal, symmetric muscle weakness. A 7yrs old girl admitted to Dept. of Pediatric, Chittagong Medical College Hospital with difficulty in stand up from sitting and lying position for 3 months, multiple erythematous papule in both upper limbs, face and extensor surface of the body for one and half months. On examination there is violaceous periorbital erythema (Heliotrope), raised papules overlying the metacarpal, interphalangeal, elbow and knee joints (Gottron’s papules). There are also erythmatous papules on both upper limbs. On laboratory examination, serum creatine kinase raised, musle biopsy showed feature of Dermatomyositis, Electromyogram reveal proximal myopathy. Based on clinical appearance, laboratory data, the diagnosis of juvenile dermatomyositis was made and treated accordingly. After initial treatment patient condition improved. She also adviced to avoid sun exposure. JCMCTA 2011; 22(2): 47-49